Interspecific differences in ecological stoichiometric characteristics of invertebrates and their influencing factors from the Beibu Gulf, China - Wang, Caiguang; Huang, Liangliang; Kang, Bin; Zhu, Liang; Liu, Hao; Zhao, Shuwen; Cheng, Yanan; Shahab, Asfandyar; Yan, Yunrong (Frontiers in Marine Science, 2024)
Invertebrates can store carbon (C), nitrogen (N), phosphorus (P), and other elements in their body tissues at theoretically homeostatic rates, thus playing an important role in the biogeochemical cycle of aquatic ecosystems. To sustain homeostasis, consumers must either balance their resource supply or adjust their stoichiometric features in response to environmental changes. However, there is limited understanding regarding potential differences in the ecological stoichiometric characteristics of marine invertebrates. To explore the ecological stoichiometric characteristics of marine invertebrates, the C, N, P, calcium (Ca), δ13C, and δ15N contents of 18 invertebrate species were analyzed from the Beibu Gulf. The results revealed that the ranges of elemental variations (C, N, and P) in invertebrates were 25.17%-47.34%, 6.14%-14.13%, and 0.26%-1.31%, respectively. The content of P in invertebrates exhibited the most significant variation, leading to alterations in C:P and N:P ratios. A significant negative correlation was observed between P content and body weight in invertebrates (p < 0.01). Furthermore, the C and N content of invertebrates were significantly negatively correlated with δ13C (p < 0.01), suggesting that the variations in C content and N content in invertebrates are influenced by different food sources, while P content varies according to body size. Our results also indicated significant interspecific differences in the ecological stoichiometry of invertebrates from the Beibu Gulf (p < 0.05). Invertebrate growth may be inhibited by P, and they do not maintain strict homeostasis, with stable homeostasis observed in higher trophic levels.